2016
DOI: 10.1093/bja/aew191
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a new scoring system to predict difficult ventilation through a supraglottic airway

Abstract: The new score for prediction of difficult ventilation through a supraglottic airway device is easy to perform and reliable, and could help anaesthetists plan for difficult airway management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
0
13
0
9
Order By: Relevance
“…14e16 In addition, any airway management method (including rescue method) can fail, but the reasons for failure have not been fully elucidated. 14,17 Furthermore, tracheal intubation might not benefit patients who are receiving cardiopulmonary resuscitation, 18,19 and it is not clear whether or not this may also be so in critically ill patients. Therefore, there are still many areas requiring study in order to improve strategies for airway management in critically ill patients.…”
Section: What Next?mentioning
confidence: 99%
“…14e16 In addition, any airway management method (including rescue method) can fail, but the reasons for failure have not been fully elucidated. 14,17 Furthermore, tracheal intubation might not benefit patients who are receiving cardiopulmonary resuscitation, 18,19 and it is not clear whether or not this may also be so in critically ill patients. Therefore, there are still many areas requiring study in order to improve strategies for airway management in critically ill patients.…”
Section: What Next?mentioning
confidence: 99%
“…With such premises, the point of difficult insertion, unless not corrected for a precise sizing policy, remains affected by a serious bias, whereas different techniques like tongue dimension-based sizing (46) show interesting but not definitive results, and further research is aiming to find out specific criteria for prediction of difficult SGAs positioning and ventilation (47).…”
Section: Sorbello and Petrini Supraglottic Airway Devices Features Amentioning
confidence: 99%
“…A validation study of a new clinical score to predict difficult ventilation through a supraglottic airway (based on the risk factors of male, age >45 years, short thyromental distance, and limited neck movements) [31] indicated that a high score is associated with a six-to sevenfold increased risk of failure. When a supraglottic airway has been inserted, its cuff should not be overinflated as it would increase the risk of pulmonary aspiration [32].…”
Section: 'Rescue Device'mentioning
confidence: 99%